Heavy metal concentrations in surface sediments and giant mudskippers, Periophthalmodon schlosseri pallas from west coast of Peninsular Malaysia and their metallothionein induction towards metal toxicity - Buhari, Tijjani Rufa'i (2012)
Assessment of heavy metals concentrations; Cu, Zn, Pb, Cd and Ni in surface sediment and giant mudskipper P. schlosseri and its metallothionein induction towards metals toxicity in the west coast of Peninsular Malaysia was conducted in the year 2008 and 2010. Surface sediments and giant mudskippers were collected in August and September 2008 and in March and June 2010 at six sampling sites. Top 3-5 cm surface sediments were collected in triplicates from each sampling sites using plastic scoop and placed in separate plastic bags which was instantly placed on ice. Fish samples were collected using trap net at the same locations were sediments were collected and placed in plastic aquarium containing some sediment and water. The surface sediments and fish samples were brought to laboratory until further analyses. Total metals concentrations and geochemical fractionation of metals in surface sediments were determined by direct aqua – regia and modified sequential extraction procedures respectively. Metallothioneins assay was conducted to determine metals induction in liver, gills and muscle. The concentrations of heavy metals in the surfaces sediment ranged from 12.79 –65.39, 60.83 – 442.19, 8.46 – 53.73, 0.6 -1.65 and 10.09 – 29.25 μg/g dry weight for Cu, Zn, Pb, Cd and Ni respectively. These values were comparable to metals concentrations in the west coast of Peninsular Malaysia and some part of the south eastern Asia. Based on fractionation analysis, effective range low (ERL), effective range medium (ERM), index of geoaccumulation (Igeo) and enrichment factor (EF) shows that metals concentrations were found higher than background concentration of world average shale, continental crust and world average sediment which might suggest anthropogenic input of metals in the study areas. Geochemical fractionation of metals revealed that of more than 66 % of Cu, Pb, Cd and Ni in surface sediments of west coast of Peninsular Malaysia were associated with resistant fraction which indicates the mobility of these metals was low. The non-resistant fraction of Zn dominated 50 % of the sampling sites suggesting anthropogenic input of Zn at these sampling sites. Heavy metals concentrations in the tissues of P. schlosseri ranged from 0.04 – 18.61, 12.79 – 152.63, 0.04 – 37.71, 0.04 – 4.42 and 0.04 – 121.84 for Cu, Zn, Pb, Cd and Ni μg/g dry weight respectively. The concentrations of metals in the tissues showed a significant difference between the sampling sites, except Cu concentration in gill which showed non-significant difference between the sampling sites. Results of Pearson’s correlation analyses showed metal concentrations in the tissues of P. schlosseri were significantly correlated with some geochemical fraction of metals in the sediment which suggest that P. schlosseri could be used as a biomonitoring agent for heavy metals pollution in the west coast of Peninsular Malaysia. The bioconcentration factor (BCF) revealed that most of the tissues of P. schlosseri were classified as macro concentrators. Liver and intestine have highest average BCF values for Cu and Zn respectively while cartilage recorded the highest BCF for Pb,Cd and Ni. These tissues might be suggested as good accumulators of the metals observed in them. The metallothioneins (MT) content in the tissues of P. schlosseri showed a significant difference between the sampling sites. The order of MT content was in the decreasing order of: liver > gill > muscle. Results of heavy metals concentrations, geochemical fractionation and pollution indices in the surface sediments revealed that the sampling sites in the present study could be classified as unpolluted, to moderately to strongly polluted. Sediment quality guideline quotient (SQG – Q) and Potential ecological risks index (RI) further indicated that the sampling sites were moderately polluted and exhibited low to moderate potential ecological risk respectively.